TINJAUAN TENTANG SISTEM PEMBAGIAN HARTA WARISAN KEPADA PARA AHLI WARIS MENURUT HUKUM ADAT SUKU BAHU POSTO ADMINISTRATIVO BAUCAU (Studi Penelitian Suku Bahu) - Celestina Gusmão; Seguito Monteiro (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The distribution of inheritance has customary inheritance requirements, namely: certainty of the death of the person who owns the property, certainty of the life of the heir when the heir dies, and knowing the causes of the status of each heir. The approach to writing this thesis is a cultural approach, which is to examine the position of each heir according to the customary law of the Bahu Tribe to obtain inheritance from the heir. New inheritance can be inherited to other parties if the testator has died, and the heirs or heirs who have the right and power to distribute the inheritance to their brothers and sisters are the first son, more entitled to regulate the inheritance left by the testator and distribute it to other heirs in accordance with existing procedures. The results of the study show that customary inheritance according to the Bahu tribal community, the heirs have the same rights, but boys and boys have higher rights than girls.